Perilaku Inovatif Kerja Serta Perceived Organizational Support Dalam Meningkatkan Kinerja Karyawan - Murtadha, Alfirda Lutfi; Kurniawan, Ignatius Soni; Lysander, Mohammad Ahyar Syafwan (Jambura Economic Education Journal, 2025)
The purpose of this study was to analyze the relationship between innovative behavior at work and perceived organizational support related to employee performance at the Department of Cooperatives, Small and Medium Enterprises, Industry, and Trade (DKUKMPP) of Bantul Regency. The sampling method used the accidental method. The distribution of questionnaires was carried out using an offline survey using quantitative methods. The location of the study was at DKUKMPP Yogyakarta Regency, with a sample of 100 employees as respondents. The data were analyzed using SPSS, and the results showed that innovative behavior at work and perceived organizational support had a positive and significant effect on the performance of DKUKMPP employees. These findings highlight the importance of organizational support and innovative behavior in increasing the productivity and effectiveness of employee performance in government agencies.